April blood : Florence and the plot against the Medicini - Martines, Lauro (London : Pimlici, 2004)
Profiles the society of fifteenth-century Florence, and discusses how certain societal aspects influenced the conspiracy against Renaissance politician Lorenzo de' Medici.
Keywords: Medici, Lorenzo de', 1449-1492; Florence (Italy) -- History -- 1421-1737.; Medici, House of; Statesmen -- Italy -- Florence